-3-s=4tj+19

Simple and best practice solution for -3-s=4tj+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-s=4tj+19 equation:


Simplifying
-3 + -1s = 4tj + 19

Reorder the terms:
-3 + -1s = 19 + 4jt

Solving
-3 + -1s = 19 + 4jt

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -1s = 19 + 3 + 4jt

Combine like terms: -3 + 3 = 0
0 + -1s = 19 + 3 + 4jt
-1s = 19 + 3 + 4jt

Combine like terms: 19 + 3 = 22
-1s = 22 + 4jt

Divide each side by '-1'.
s = -22 + -4jt

Simplifying
s = -22 + -4jt

See similar equations:

| 8(1.25-1.125x)+9x=10 | | 4*12+8*0.8=40 | | 24=m-15 | | 4*10+8*0.8=40 | | 4*4.6+8*0.8=40 | | 16x+12y=136 | | b=32(1600) | | 1/5*8-2/3*15=30 | | 1/5*4-2/3*15=30 | | 25+3y=21+38y | | b=32a | | 1/5*x-2/3*15=30 | | 2-3x=x-8 | | 1/5x-2/3*15=30 | | 23+36y=3+5y | | w+w-5=23 | | 120+f+60+15+20=130+35+2f+0 | | x^2-25x+76=0 | | 4=a/8 | | 3x+6=-48-6x | | log(4x+7)-log(x-1)=1 | | 2x+4+2x+2=x+10 | | wat=396 | | 8x-8y=-136 | | (12+x)+(6x+2)=80 | | 0.05x=2.90 | | log(3t)=0.8 | | 2(x+4)-2=5x-3(-1+x) | | (8x+30)+(4x+18)=180 | | 7ln(x-3)=1 | | 10b^2+17b+3= | | 41.5=6x-3.5 |

Equations solver categories